Strategic Entrepreneurship: The case of Infynita Inc., in Pune (India) - Godhwani, Tina (2008)
Most small businesses fail to make it big even after they effectively identify gaps in the market. The reason often being their inability to integrate opportunity-seeking and advantage-seeking behaviors to sustain a competitive advantage. Thus this study applies Ireland et al.s (2003) model of strategic entrepreneurship to a software company in India, Infynita Inc., in an attempt to identify where small to medium sized enterprises (SMEs) such as Infynita Inc. go wrong after they successfully identify entrepreneurial opportunities. The study holds focus in four key areas, as per Ireland et al.s (2003) model, namely: (1) entrepreneurial mindset, (2) entrepreneurial culture and entrepreneurial leadership, (3) managing resources strategically and (4) applying creativity and developing innovation. Along with this, this research attempts to indicate the usefulness of the model which is primarily based on a literature review.